2023
DOI: 10.1108/lodj-03-2022-0121
|View full text |Cite
|
Sign up to set email alerts
|

Impact of servant leadership on innovative work behaviour: a moderation mediation analysis

Abstract: PurposeThe aim of this paper is to investigate the effect the servant leadership on innovative work behaviour (IWB) of teachers. Besides this, the mediating effect of ambidexterity on enhancing IWB and moderating role of gender has also been investigated.Design/methodology/approachVariance-based SEM has been used for testing the proposed structural model with a sample of 350 college teachers.FindingsFindings of the study revealed that servant leadership positively influences IWB. Additionally, IWB can be augme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 111 publications
(206 reference statements)
1
2
0
Order By: Relevance
“…The present study's statistical analysis demonstrates a strong and positive association between servant leadership and innovative work behavior (IWB), consistent with the findings of Kaya & Karatepe (2020) and Shailja et al (2023). Servant leadership is a leadership style characterized by prioritizing the needs of followers, emphasizing visioning, modeling through personal example, mentoring, and empowering.…”
Section: The Effect Of Servant Leadership On Innovative Work Behaviorsupporting
confidence: 88%
See 2 more Smart Citations
“…The present study's statistical analysis demonstrates a strong and positive association between servant leadership and innovative work behavior (IWB), consistent with the findings of Kaya & Karatepe (2020) and Shailja et al (2023). Servant leadership is a leadership style characterized by prioritizing the needs of followers, emphasizing visioning, modeling through personal example, mentoring, and empowering.…”
Section: The Effect Of Servant Leadership On Innovative Work Behaviorsupporting
confidence: 88%
“…It also ensures that work is distributed in a fair and equal manner, taking into account each person's individual abilities (Rabiul & Yean, 2021). Some examples of research of this topic in service industry are: in high-tech company (Su et al, 2020), school institutions (Anshori et al, 2023;Hermanto & Srimulyani, 2022), hotel (Ling et al, 2016), college teachers (Shailja et al, 2023), and public company (Chen et al, 2022). These studies have found that servant leadership enhance job engagement (Kaya & Karatepe, 2020), innovative work behavior (Dayanti & Yulianti, 2023;Shailja et al, 2023;Su et al, 2020;Yoshida et al, 2014), creative process engagement (Chen et al, 2022), higher performance (Hermanto & Srimulyani, 2022), organizational citizenship behavior and extra role behavior (Hermanto & Srimulyani, 2022), and career satisfaction (Kaya & Karatepe, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation